2010
DOI: 10.2337/dc10-0646
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Time Points to Calculate the Composite Index

Abstract: S ince the original publication of the composite (Matsuda) index for the measurement of insulin sensitivity from plasma glucose and insulin concentrations during the oral glucose tolerance test (OGTT) (1), this index has been widely used by investigators throughout the world. According to Scopus, more than 1,000 articles have cited the original article (1) during the last 10 years, and several modifications of this index have been published (2,3). Although the basic idea is to use the plasma insulin and glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
185
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(189 citation statements)
references
References 3 publications
4
185
0
Order By: Relevance
“…G 0 and G 120 represent plasma glucose concentrations at times 0 and 120 minutes, and I 0 and I 120 represent insulin concentrations at times 0 and 120 minutes. Units for the ISI(composite) are mg×mU/dL×L 19. The Gutt ISI 0,120 was calculated as ISI 0,120 =m/[G×log 10 (I)], in which m=[75 000 mg+(fasting glucose−2‐hour glucose)×0.19×body weight kg]/120 minutes, G represents mean fasting and 2‐hour glucose concentrations, and I represents mean fasting and 2‐hour insulin concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…G 0 and G 120 represent plasma glucose concentrations at times 0 and 120 minutes, and I 0 and I 120 represent insulin concentrations at times 0 and 120 minutes. Units for the ISI(composite) are mg×mU/dL×L 19. The Gutt ISI 0,120 was calculated as ISI 0,120 =m/[G×log 10 (I)], in which m=[75 000 mg+(fasting glucose−2‐hour glucose)×0.19×body weight kg]/120 minutes, G represents mean fasting and 2‐hour glucose concentrations, and I represents mean fasting and 2‐hour insulin concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The HbA1c (Japan Diabetes Society; JDS) values were converted to National Glycohemoglobin Standardization Program (NGSP) values using the formula developed by the JDS (see below). [9] In addition, insulin sensitivity was calculated with the simple insulin sensitivity index, as follows: [10,11] (1) HbA1c = [HbA1c (JDS)(%)×1.02+0.25(%)] Diabetes is defined in accordance with the American Diabetes Association (ADA) guidelines [12] as an FPG level ≥126 mg/dL, a 2-hour plasma glucose level during a OGTT ≥200 mg/dL, or an HbA1c concentration ≥6.5%. Subjects with an FPG level <100 mg/dL, a 2-hour plasma glucose level during the OGTT <140 mg/dL, and an HbA1c level <5.7% are defined as having normal glucose tolerance.…”
Section: Data Collection and Handlingmentioning
confidence: 99%
“…They were 50±9 years old and 1453 subjects (85%) were male. Plasma glucose and insulin were measured at 0 and 120 min during the 75-g OGTT, from which the Matsuda index 3) and HOMA-IR 2) were calculated. The current analyses were performed after dividing the population randomly into two groups; one group (n = 860) was used as the training data, for model derivation, and the other (n = 859) as the test data, for model validation.…”
Section: Insulin Resistance Can Be Easily Estimated By Body Mass Indementioning
confidence: 99%
“…We read with great interest the recent report by Oka and colleagues 1) , who successfully assessed the association of visceral and subcutaneous adipose tissue with insulin resistance in a Japanese population, using the homeostasis model for the assessment of insulin resistance (HOMA-IR) 2) and the Matsuda index 3) as indices of insulin resistance/sensitivity. Their detailed investigations also showed that body mass index (BMI) was not inferior in predicting insulin resistance to the area of visceral fat tissue evaluated by computed tomography.…”
Section: To the Editormentioning
confidence: 99%